2020
DOI: 10.3390/app10082887
|View full text |Cite
|
Sign up to set email alerts
|

Review on Development of High-Static–Low-Dynamic-Stiffness Seat Cushion Mattress for Vibration Control of Seating Suspension System

Abstract: This review focuses on studying passive vibration isolation techniques and their applications. Advantages and disadvantages of different vibration isolation techniques will be compared in order to find an innovative method to reduce seating suspension system vibration and improve the ride comfort of vehicles’ drivers. Quasi-zero stiffness (QZS) isolators of high-static–low-dynamic stiffness are found to have good application prospects in low-frequency vibration isolation. In order to improve the isolation perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Therefore, drivers operating in sectors such as mining, construction, and agriculture who spend many hours a day on the road are particularly vulnerable to the potentially harmful vibrations that result from poor road conditions. Studies have shown low frequency, whole-body vibrations could cause various health issues, including increased tiredness, fatigue, motion sickness, vertebrae diseases, digestive and vision issues, balance impairment, and a reduction in reaction times [23]. Due to the glaring consequences of vibration on the health of off-road vehicle drivers, industry players have considered it a critical factor in the design and manufacturing of automotive vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, drivers operating in sectors such as mining, construction, and agriculture who spend many hours a day on the road are particularly vulnerable to the potentially harmful vibrations that result from poor road conditions. Studies have shown low frequency, whole-body vibrations could cause various health issues, including increased tiredness, fatigue, motion sickness, vertebrae diseases, digestive and vision issues, balance impairment, and a reduction in reaction times [23]. Due to the glaring consequences of vibration on the health of off-road vehicle drivers, industry players have considered it a critical factor in the design and manufacturing of automotive vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Low-frequency vibration widely exists in engineering structures [23] . Currently, utilizing metamaterials to suppress low-frequency vibration propagation along the engineering structures has aroused great concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Applying this advantage, this design is successfully applied to the gravity counteraction for astronautic device tests [2][3] and gravity meter [4] . Now, it has been widely studied for more than 60 years [5][6] . The key of QZS is to realize the negative stiffness [7] .…”
Section: Introductionmentioning
confidence: 99%